A community paradigm of organized crime - Potter, Gary (American journal of criminal justice, 1990)
This article reviews the available empirical research on organized crime and suggests that an important dimension of that research is the close symbiosis between organized crime groups and the communities in which they operate. As such, it is hypothesized that the concept of community may be important to explaining the persistence and durability of organized crime. A community model proposed by Roland Warren, which seeks to integrate much of the sociological literature on the community, and which delineates the basic functions of the community is presented as a means of organizing the available date about organized crime and explaining organized crime’s functional and latent aspects.